2008
DOI: 10.4103/0250-474x.45404
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of antidiabetic drugs in Indore city hospital

Abstract: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia, glycosuria, and sometimes ketonemia. The present study was carried out to assess prescribing practice and general trend of diabetes among patients at the Bombay Hospital, Indore. Prescriptions and complete records of diabetic patients were monitored and data was filed as per WHO prescription proforma. The study revealed that prescription of metformin (27%) and glimepiride (22.60%) were found to be maximum among various available antidiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
38
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 6 publications
21
38
2
Order By: Relevance
“…Our study findings are also similar to the study conducted in Texas that hypertension is more common complication affecting 20-60% of people with diabetes [22].…”
Section: Discussionsupporting
confidence: 82%
“…Our study findings are also similar to the study conducted in Texas that hypertension is more common complication affecting 20-60% of people with diabetes [22].…”
Section: Discussionsupporting
confidence: 82%
“…This is in comparison to other studies done in India. [5,6] The most common co-morbid condition was hypertension which is similar to study done by Abdi SH etal,2012 and Arauz-Pacheco etal,2002. [6,7] The present study revealed that the most common drug to be prescribed at the time of discharge was metformin but during the stay was insulin.…”
Section: Discussionsupporting
confidence: 77%
“…Co-prescription of a biguanides and sulfonylurea is a common practice. [23] Adding a second agent is usually better than increasing the dosage of an agent that has already been given in a nearly maximum dosage. In some patients three drug combinations may be useful.…”
Section: Discussionmentioning
confidence: 99%